2016
DOI: 10.1186/s13071-016-1612-4
|View full text |Cite
|
Sign up to set email alerts
|

Selenophene and thiophene-core estrogen receptor ligands that inhibit motility and development of parasitic stages of Haemonchus contortus

Abstract: BackgroundParasitic worms represent a substantial disease burden in animals and humans worldwide. The control of parasitic roundworms (nematodes) relies heavily on the use of anthelmintic drugs. However, widespread drug resistance in nematodes seriously compromises the effectiveness of many anthelmintics around the world. Thus, there is a need to discover new drugs, with unique modes of action, against parasites.MethodsHere, we synthesised and tested 74 selective estrogen receptor modulators (SERMs) for in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…This difference in potency might be due to variation in expression of its target(s) in the nematode, a distinction in physiology between these two developmental stages of the worm and/or the nature and extent of the uptake of the compound by the worm. An integrated use of transcriptomic, proteomic and metabolomic techniques ( Mikami et al., 2012 , Schwarz et al., 2013 , Preston et al., 2016c ) might be able to elucidate the physiological and biological pathways in H. contortus and/or other worms affected by SN00797439.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in potency might be due to variation in expression of its target(s) in the nematode, a distinction in physiology between these two developmental stages of the worm and/or the nature and extent of the uptake of the compound by the worm. An integrated use of transcriptomic, proteomic and metabolomic techniques ( Mikami et al., 2012 , Schwarz et al., 2013 , Preston et al., 2016c ) might be able to elucidate the physiological and biological pathways in H. contortus and/or other worms affected by SN00797439.…”
Section: Discussionmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) was used to assess whether deguelin causes structural damage to the larval stages of H. contortus, as previously described (43). In brief, deguelin and positive control compounds-monepantel and moxidectinwere each diluted to a final concentration of 100 mM in LB* and incubated with exsheathed L3s or L4s in wells of a 96-well plate at a density of 6000 larvae/ml for 24 h at 38°C and 10% CO 2 .…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…In addition, a number of biologically active selenaheterocycles, such as cytoprotective agent ebselen, have recently been discovered . Moreover, we and other found that a few selenophene compounds inhibited the motility and development of stages of the comparable nematode Haemonchus contortus . More recently, fluselenamyl, a novel planar benzoselenazole derivative, was used as a PET imaging agent for amyloid in Alzheimer's disease (Figure )…”
Section: Introductionmentioning
confidence: 98%